Unpublished work by Ricardo Bruno Mendes Gonçalves - Naomar Almeida Filho; José Ricardo Ayres (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
This editorial centers on a previously unpublished work by Ricardo Bruno Mendes Gonçalves, recently published in Salud Colectiva, in which he considers the relationship between epidemiology and medical practice, arriving at a novel interpretation of the health sciences as a foundation for democracy. The text is based on an inaugural lecture delivered on December 16, 1988 as part of a seminar called "Clinical epidemiology: possible scientific field or new medical ideology?" organized by the Department of Preventive Medicine at the Universidade Federal da Bahia, Brazil.